2019
DOI: 10.24191/ajue.v15i3.7801
|View full text |Cite
|
Sign up to set email alerts
|

Digital Storytelling for 21st Century Learning: A Study on Pre-Service Teachers’ Perception

Abstract: Digital Storytelling is one of the new pedagogical tools that call upon students’ creativity and helps them to “learn by doing”. It is one of the important steps towards creating the 21st-century learning environment as it promotes the integration of student-centred and technology-enriched learning environment for learners. Despite the many benefits that this learning tool has to offer, many educators are still reluctant to integrate this kind of technology in their classes which resulted in low implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…The learners use their prior knowledge as they create the video, and hence their self-confidence increases with time. 3 Dalim et al (2019) In the study conducted among pre-service teachers, it was found that DS is a teaching approach that can nurture positive values such as collaborative learning, active learning engagement, critical thinking skills, and creativity among the learners. It was found that the learners engage more actively when DS was employed as it provides an environment for the learners to explore and learn.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The learners use their prior knowledge as they create the video, and hence their self-confidence increases with time. 3 Dalim et al (2019) In the study conducted among pre-service teachers, it was found that DS is a teaching approach that can nurture positive values such as collaborative learning, active learning engagement, critical thinking skills, and creativity among the learners. It was found that the learners engage more actively when DS was employed as it provides an environment for the learners to explore and learn.…”
Section: Resultsmentioning
confidence: 99%
“…The various research design employed by the researchers shows the diversity of DS. Although Okumus (2020), Dalim et al (2019), Jantakoon et al (2019), and Preradovic at al. (2016) used quantitative-Quasi-Experimental research design in their study, the number of participants in their studies varied from 15 to 150 participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that the mean pre-service teacher score in the survey was above 3 revealed that according to the views of the pre-service teachers, DS developed the 21st-century skills. The advocates of DS argue that the DS leads to the acquisition of 18 out of 20 21st century skills (Dalim et al, 2019;Ekmekçi, 2016;Kocaman Karoğlu, 2015;Jakes, 2006;Niemi et al, 2014;Seçkin Kapucu & Yurtseven Avci, 2020).…”
Section: Discussionmentioning
confidence: 99%